Astragaloside IV Suppresses High Glucose-Induced NLRP3 Inflammasome Activation by Inhibiting TLR4/NF-κB and CaSR - Bin Leng; Yingjie Zhang; Xinran Liu; Zhen Zhang; Yang Liu; Hongxin Wang; Meili Lu (Mediators of Inflammation)
Long-term exposure to high glucose induces vascular endothelial inflammation that can result in cardiovascular disease. Astragaloside IV (As-IV) is widely used for anti-inflammatory treatment of cardiovascular diseases. However, its mechanism of action is still not fully understood. In this study, we investigated the effect of As-IV on high glucose-induced endothelial inflammation and explored its possible mechanisms. In vivo, As-IV (40 and 80 mg/kg/d) was orally administered to rats for 8 weeks after a single intraperitoneal injection of streptozotocin (STZ, 65 mg/kg). In vitro, human umbilical vein endothelial cells (HUVECs) were treated with high glucose (33 mM glucose) in the presence or absence of As-IV, NPS2143 (CaSR inhibitor), BAY 11-7082 (NF-κB p65 inhibitor), and INF39 (NLRP3 inhibitor), and overexpression of CaSR was induced by infection of CaSR-overexpressing lentiviral vectors to further discuss the anti-inflammatory property of As-IV. The results showed that high glucose increased the expression of interleukin-18 (IL-18), interleukin-1β (IL-1β), NLRP3, caspase-1, and ASC, as well as the protein level of TLR4, nucleus p65, and CaSR. As-IV can reverse these changes in vivo and in vitro. Meanwhile, NPS2143, BAY 11-7082, and INF39 could significantly abolish the high glucose-enhanced NLRP3, ASC, caspase-1, IL-18, and IL-1β expression in vitro. In addition, both NPS2143 and BAY 11-7082 attenuated high glucose-induced upregulation of NLRP3, ASC, caspase-1, IL-18, and IL-1β expression. In conclusion, this study suggested that As-IV could inhibit high glucose-induced NLRP3 inflammasome activation and subsequent secretion of proinflammatory cytokines via inhibiting TLR4/NF-κB signaling pathway and CaSR, which provides new insights into the anti-inflammatory activity of As-IV.